Defining photometric peculiar type Ia Supernovae - González Gaitán, S. (2014)
We present a new photometric identification technique for SN 1991bg-like type Ia supernovae (SNe Ia), i.e., objects with light curve characteristics such as later primary maxima and the absence of a secondary peak in redder filters. This method is capable of selecting this sub-group from the normal type Ia population. Furthermore, we find that recently identified peculiar sub-types such as SNe Iax and super-Chandrasekhar SNe Ia have photometric characteristics similar to 91bg-like SNe Ia, namely, the absence of secondary maxima and shoulders at longer wavelengths, and can also be classified with our technique. The similarity of these different SN Ia sub-groups perhaps suggests common physical conditions. This typing methodology permits the photometric identification of peculiar SNe Ia in large upcoming wide-field surveys either to study them further or to obtain a pure sample of normal SNe Ia for cosmological studies.